Peritoneal sepsis: patient characteristics relaparotomized.: Incidence - Opportunity - Prognostic Factors - Medina, Julio; Pontet, Julio; Curbelo, Andrea; Ferra, Pablo; Freire, Ana; Misa, Ricardo; Bentancourt, Solveig (Cirugía del Uruguay, 2004)
Patients suffering from severe sepsis originating in the abdominal-peritonea/ region frequently require re-interventions, as this condition persists with high morbility Management of therapy is difficu/t and tends to be controversia/; existing studies consider a universe which that is far from homogenic. The analysis covers a five-year period. Case material involved 55 patients with severe abdominal sepsis requiring at)east one re-laparotomy. lt takes into considerations the incidence, c/inica/ manifestations leading to a positive re-laparotomy, deathrate and factors involved in prognosis. The absence of multi-organic dysfunction (MOD) was considered a va/id criteria far exclusion